Osteoarthritis grades no affects gait analysis in middle-age and elderly’s women. A cross-sectional study - James Sepulveda; Esteban Aedo Muñoz; Manuel Lobos-González; Jaime Verdugo-Bosh; Amaya Prat-Luri; Ciro Brito; Bianca Miarka; Jorge Cancino-Jimenéz; Leonidas Arias-Poblete (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Aging is habitually related to modifications in the peripheral, central nervous and musculoskeletal systems. These modifications are frequently associated with mobility complications. It is currently considered that the spatiotemporal gait parameters (SGP) may be good functional indicators of the severity of knee osteoarthritis (KOA). Objective: to compare the SGP in middle-age and older women with different radiographic KOA diagnosis. Methods and materials: For this, ninety-nine (99) female participants (age: 61.0±3.0 years; body mass: 72.9±13.4 kg; height: 1.5±0.1 m; BMI: 31.2±5.7 Kg/m2) were enrolled in a cross-sectional design. All participants were classified according to the Kellgren-Lawrence radiological scale (None n=15; Doubtful n=24; Minimal n=22; Moderate n=20 and Severe n=18). All participants performed a 25-m Walk test for which the SGP was measured (cadence, duration of monopodal support phase, and stride length). Results: No differences were observed in any SGP measures (cadence, p=0.57; monopodal support phase, p=0.65; and stride length, p=0.22). Conclusion: Our results showed that there is no agreement between the SGP and radiographic KOA diagnosis.